Wütende Texte Die Sprache heißen Zorns in der deutschen Literatur des 20. Jahrhunderts - Stumm, Alfred (Hermaea. Neue Folge, 2022)
The furious text has not been an object of systematic analysis until now. In this volume, this analysis is based on an interdisciplinary definition of the emotion of fury itself. Text analyses thus provide insights that go beyond previous findings from the fields of poetics, rhetoric, linguistics, and psychology. Although this study takes up the theory of satire, it develops a new approach to categorize and analyze aggressive writing.